2013
DOI: 10.1002/jgra.50111
|View full text |Cite
|
Sign up to set email alerts
|

Observation of hole Peregrine soliton in a multicomponent plasma with critical density of negative ions

Abstract: [1] The evolution of hole Peregrine soliton (appearing as a deep trough between two crests) from ion-acoustic perturbations excited in a multicomponent plasma with critical density of negative ions has been observed. The observed soliton is described by the rational solution of the cubic nonlinear Schrödinger equation, which can appear as an isolated high peak or a deep hole depending on the phase of the underlying carrier wave relative to the envelope. The measured amplitude of the hole Peregrine soliton (dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…The observations of the same doubly-localized breathers in optical fibers [14,15] as well as in deep-water [16,17] emphasize the necessity of discussing analogies in the interaction between dispersion and nonlinearity in the description of modulationally unstable wave packets [18] for nonlinear dispersive media, satisfying the focusing regime condition. Interestingly, the experimental investigations of breather dynamics in optical fibers have motivated a new experimental field of research in water waves [19,20] as well as in plasma [21]. In fact, the modulation instability (MI) [22], also referred to as the Benjamin-Feir instability [23], is a fundamental mechanism that describes and quantifies the formation of extreme wave events in a one-dimensional wave field propagation.…”
Section: Introductionmentioning
confidence: 99%
“…The observations of the same doubly-localized breathers in optical fibers [14,15] as well as in deep-water [16,17] emphasize the necessity of discussing analogies in the interaction between dispersion and nonlinearity in the description of modulationally unstable wave packets [18] for nonlinear dispersive media, satisfying the focusing regime condition. Interestingly, the experimental investigations of breather dynamics in optical fibers have motivated a new experimental field of research in water waves [19,20] as well as in plasma [21]. In fact, the modulation instability (MI) [22], also referred to as the Benjamin-Feir instability [23], is a fundamental mechanism that describes and quantifies the formation of extreme wave events in a one-dimensional wave field propagation.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear Schrödinger equation (NLSE) admits interesting rational solutions named rogue waves (RWs), also known as freak waves, extreme waves, and killer waves, in the MI region. Sharma and Bailung [35] have also experimentally found peregrine soliton in a multi-component plasma with a critical density of negative ions. Researchers have devoted their attention to solve the mystery of these colossal waves because of their intrinsically arbitrary nature and their complex formation mechanisms.…”
Section: Introductionmentioning
confidence: 92%
“…The field of MI and RWs has been considered one of the highly interdisciplinary areas of research involving plasma physics, [12] oceanography, [28] Bose-Einstein condensation, [29] optics, [30] superfluid helium, [31] and even finance [32] A number of authors have theoretically studied different criteria of MI and RWs in many PIPM [3,12,33] and confirmed them in laboratory experiments. [34][35][36] Bailung et al [34] have observed peregrine solitons in a multi-component plasma with negative ions. Sharma and Bailung [35] have also experimentally found peregrine soliton in a multi-component plasma with a critical density of negative ions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The features of rogue waves have been theoretically investigated in many plasma systems [31][32][33][34][35][36][37][38] and confirmed in experiments. 39,40 The aim of this paper is to investigate the propagation of rogue waves in an ion-beam plasma containing negative ions, positive ions, and superthermal electrons with a kappa-type distribution. We take into account dissipative mechanisms, including ionization, negative-positive ion recombination, and electron attachment, in the plasma model.…”
Section: Introductionmentioning
confidence: 99%